Studying Planarian Regeneration Aboard the International Space Station Within the Student Space Flight Experimental Program - , Vista SSEP Mission 11 Team; Hagstrom, Danielle; Bartee, Christine; Collins, Eva-Maria S. (Frontiers in Astronomy and Space Sciences, 2018)
The growing possibilities of space travel are quickly moving from science fiction to reality. However, to realize the dream of long-term space travel, we must understand how these conditions affect biological and physiological processes. Planarians are master regenerators, famous for their ability to regenerate from very small parts of the original animal. Understanding how this self-repair works may inspire regenerative therapies in humans. Two studies conducted aboard the International Space Station (ISS) showed that planarian regeneration is possible in microgravity. One study reported no regenerative defects, whereas the other study reported behavioral and microbiome alterations post-space travel and found that 1 of 15 planarians regenerated a Janus head, suggesting that microgravity exposure may not be without consequences. Given the limited number of studies and specimens, further microgravity experiments are necessary to evaluate the effects of microgravity on planarian regeneration. Such studies, however, are generally difficult and expensive to conduct. We were fortunate to be sponsored by the Student Spaceflight Experiment Program (SSEP) to investigate how microgravity affects regeneration of the planarian species Dugesia japonica on the ISS. While we were unable to successfully study planarian regeneration within the experimental constraints of our SSEP Mission, we systematically analyzed the cause for the failed experiment, leading us to propose a modified protocol. This work thus opens the door for future experiments on the effects of microgravity on planarian regeneration on SSEP Missions as well as for more advanced experiments by professional researchers.